Clinical Trials of Poly(ADP-Ribose) Polymerase Inhibitors for Cancer Therapy: A Review - Buege, Michael; B. Mahajan, Pramod (Reviews on Recent Clinical Trials, 2015)
Poly(ADP-Ribose) Polymerase (PARP) is a family of enzymes involved in DNA repair, genome stability, cellular energy metabolism and cell division. Inhibition of PARP-1, the wellcharacterized member of this family, has been explored as a strategy for enhancing anti-cancer activity of existing drugs and for developing new drugs. Recently unique enzymatic properties and biological functions of PARP-2 and PARP-3 have been discovered, further expanding the utility of PARP as a target for cancer pharmacotherapy. We compare and contrast the structural and enzymatic properties of these three members of the PARP family. Interactions of these enzymes with proteins specific to different DNA repair pathways are summarized. Further, we evaluate progress on development of PARP inhibitors as anticancer agents. Results of Phase I and Phase II clinical trials of seven PARP inhibitors, used alone or in combination with known anticancer agents are reviewed highlighting common observations regarding the maximum tolerable dose, adverse reactions profile, PARP inhibition and anticancer effects. While further clinical studies are warranted, based on current data, Olaparib (Ola), Veliparib (Veli) and Rucaparib (Ruca) offer considerable potential. Prolonged exposure to Ola and Veli leads to resistant cancer cells, primarily through restoration of the HR pathway, overexpression of the P-glycoprotein efflux pump or modulation of PARP expression. Some resistant cancer cells continue to respond to platinum based drugs, encouraging further development of PARP inhibitors for cancer treatment. Future course of this research, specifically focusing on use of PARP inhibition as a strategy for personalized cancer therapy, is discussed.
Keywords: ADP-Ribosylation